Answer: C.
![Mx+Ny=P\\(2M-R)x+(2N-S)y=P-2](https://tex.z-dn.net/?f=Mx%2BNy%3DP%5C%5C%282M-R%29x%2B%282N-S%29y%3DP-2)
Step-by-step explanation:
Given: The system
has the solution (1,3), where M,N,P,R,S and T are non zero real numbers.
A.
![Mx+Ny=P\\ 7Rx+7Sy=7T](https://tex.z-dn.net/?f=Mx%2BNy%3DP%5C%5C%207Rx%2B7Sy%3D7T)
Divide 7 on both sides on the second equation , we will get
![Mx+Ny=P\\ Rx+Sy=T](https://tex.z-dn.net/?f=Mx%2BNy%3DP%5C%5C%20Rx%2BSy%3DT)
Thus, this system has solution (1,3)
B.
![(M+R)x+(N+S)y=P+T.......(1)\\\\ 7Rx+7Sy=7T................(2)](https://tex.z-dn.net/?f=%28M%2BR%29x%2B%28N%2BS%29y%3DP%2BT.......%281%29%5C%5C%5C%5C%207Rx%2B7Sy%3D7T................%282%29)
Subtract equation (2) from equation (1), we get
![Mx+Ny=P\\ Rx+Sy=T](https://tex.z-dn.net/?f=Mx%2BNy%3DP%5C%5C%20Rx%2BSy%3DT)
Thus, this system has solution (1,3)
C.
![Mx+Ny=P...........(1)\\\\(2M-R)x+(2N-S)y=P-2T............(2)](https://tex.z-dn.net/?f=Mx%2BNy%3DP...........%281%29%5C%5C%5C%5C%282M-R%29x%2B%282N-S%29y%3DP-2T............%282%29)
We can rewrite the equation (2) as
![2Mx-Rx+2Ny-Sy=P-2T............(3)](https://tex.z-dn.net/?f=2Mx-Rx%2B2Ny-Sy%3DP-2T............%283%29)
Multiply 2 on both sides of equation (1), we get
![2Mx+2Ny=2P.........(4)](https://tex.z-dn.net/?f=2Mx%2B2Ny%3D2P.........%284%29)
Subtract equation (3) from (4), we get
![Rx+Sy=P+2T](https://tex.z-dn.net/?f=Rx%2BSy%3DP%2B2T)
But ![Rx+Sy=T](https://tex.z-dn.net/?f=Rx%2BSy%3DT)
Thus, this system does not have solution as (1,3).
D.
![\frac{M}{2}+\frac{N}{2}=\frac{P}{2}\\\\Rx+Sy=T](https://tex.z-dn.net/?f=%5Cfrac%7BM%7D%7B2%7D%2B%5Cfrac%7BN%7D%7B2%7D%3D%5Cfrac%7BP%7D%7B2%7D%5C%5C%5C%5CRx%2BSy%3DT)
Multiply 2 on both sides on the first equation , we will get
Thus, this system has solution (1,3)